PENGARUH METODE TPR (TOTAL PHYSICAL RESPONSE) TERHADAP PENINGKATAN KECERDASAN LINGUSITIK ANAK USIA DINI PADA KELOMPOK B TK MELATI DESA SIKUR - Samsul Mujtahidin; Sry Anita Rachman (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
The purpose of this study was to see the effect of the TPR (total physical response) method on increasing linguistic intelligence in group B early childhood TK Melati Sikur Village. This study used a quantitative research approach with a pre-experimental type and a one group pretest-posttest research design. The research subjects were 27 children. Methods of data collection used observation, test and documentation. Data analysis used a statistical non-parametric level test marked Wilcoxon (Wilcoxon match pairs test). Based on the results of data analysis on linguistic-verbal intelligence at the time of initial observation (pre-test) and post-test Physical Response) shows that the average value of children's linguistic intelligence before using the TPR method is included in the sufficient category. Whereas after using the TPR method in group B early childhood TK Melati Sikur Village experienced an increase to a good category. This can be interpreted that there is an influence of the TPR (Total Physical Response) method on increasing the linguistic intelligence of early childhood group B TK Melati Sikur Village.